Mapping of regional lung microstructural parameters using hyperpolarized 129Xe dissolved‐phase MRI in healthy volunteers and patients with chronic obstructive pulmonary disease. Issue 4 (26th October 2018) - Kern, Agilo L.; Gutberlet, Marcel; Voskrebenzev, Andreas; Klimeš, Filip; Rotärmel, Alexander; Wacker, Frank; Hohlfeld, Jens M.; Vogel‐Claussen, Jens
Abstract : Purpose: To develop a novel technique for voxel‐based mapping of lung microstructural parameters using hyperpolarized 129 Xe dissolved‐phase MR imaging during saturation recovery. Methods: A pulse sequence using a highly undersampled stack‐of‐stars trajectory was developed, and low‐rank plus sparse matrix decomposition was employed for reconstruction of regional 129 Xe uptake dynamics into lung tissue. In 4 healthy volunteers and 9 patients with chronic obstructive pulmonary disease, the technique was tested and compared to chemical shift saturation recovery spectroscopy in patients. Reproducibility of 129 Xe gas uptake imaging was assessed by computing coefficients of variation, and results were compared with other modalities. Results: Numerical simulations and results from in vivo measurements in patients with chronic obstructive pulmonary disease showed that septal wall thickness and surface‐to‐volume ratio can be measured with an accuracy close to spectroscopic measurements. The average of the microstructural parameters of the total lung volume showed good reproducibility (coefficient of variation wall thickness: 7.4% coefficient of variation surface‐to‐volume ratio: 7.5%) and correlated strongly with the findings of global chemical shift saturation recovery spectroscopy. Gravitational gradients of microstructural parameters and increased heterogeneity in chronic obstructive pulmonary disease patients were observed. Conclusion: A novel technique for mapping of regional lung microstructural parameters was introduced, and its feasibility was shown in healthy volunteers and chronic obstructive pulmonary disease patients.